Revision of 1875: The General Statutes of the State of Connecticut, with the Declaration of Independence, the Constitution of the United States, and the Constitution of Connecticut 529 (1875) - (:unkn) unknown (My University, 1832)
§ 27: individuals who refuse to remove any gun-powder when legally requests by the selectmen of the town where the powder is deposited or kept shall forfeit fifty dollars.
Keywords: GUNPOWDER - STORAGE